2023
DOI: 10.1021/jacs.3c08854
|View full text |Cite
|
Sign up to set email alerts
|

Label-Free High-Resolution Photothermal Optical Infrared Spectroscopy for Spatiotemporal Chemical Analysis in Fresh, Hydrated Living Tissues and Embryos

Nika Gvazava,
Sabine C. Konings,
Efrain Cepeda-Prado
et al.

Abstract: Label-free chemical imaging of living and functioning systems is the holy grail of biochemical research. However, existing techniques often require extensive sample preparation to remove interfering molecules such as water, rendering many molecular imaging techniques unsuitable for in situ structural studies. Here, we examined freshly extracted tissue biopsies and living small vertebrates at submicrometer resolution using optical photothermal infrared (O-PTIR) microspectroscopy and demonstrated the following m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 63 publications
0
3
0
Order By: Relevance
“…MIP was also used to detect amyloid plaques rich in β-sheet structures in the freshly extracted tissue . Additionally, in this study, time-resolved MIP images were demonstrated.…”
Section: Life Science Applicationsmentioning
confidence: 88%
See 1 more Smart Citation
“…MIP was also used to detect amyloid plaques rich in β-sheet structures in the freshly extracted tissue . Additionally, in this study, time-resolved MIP images were demonstrated.…”
Section: Life Science Applicationsmentioning
confidence: 88%
“…These applications encompass the analysis of proteins, carbohydrates, lipids, enzymes, nucleic acids, ranging from individual nanometer scale viruses to centimeter-scale tissue samples. Several notable examples of this include the demonstration of stable isotope probing in microbiological studies by the Goodacre group at Liverpool University, isotope-labeled cell metabolism by the Davis group at Yale University, , and label-free analysis of degenerative disease metabolism by Oxana Klementieva and colleagues at Lund University. In parallel, the Ideguchi group at the University of Tokyo imaged water exchanges in living cells . The Kosik group at the University of California Santa Barbara mapped azide-tagged fatty acids in human-derived model systems .…”
Section: History Of Developmentmentioning
confidence: 99%
“…Chemical analysis is central to all fields of science, technology, engineering, and health. Strategies for the analysis of ions and organics include optical, electrochemical, and chromatographic methods . Optical methods often lack selectivity and generally require large and expensive instrumentation, and mainstream chromatographic instruments remain far from portable and inexpensive .…”
Section: Introductionmentioning
confidence: 99%